درجة توافر كفايات استخدام تقنيات التعليم لدى معلمي اللغة العربية في الحلقة الثانية من التعليم الأساسي ومستوى ممارستهم لها "دراسة ميدانية في مدارس مدينة دمشق" - صيام, محمد وحيد; سكرية, جميلة عبد القادر (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث إلى تعرّف توافر كفايات استخدام تقنيات التعليم لدى معلمي اللغة العربية في الحلقة الثانية من التعليم الأساسي ومستوى ممارستهم لها في مدارس مدينة دمشق، ولتحقيق هدف البحث قامت الباحثة بتصميم استبانة تضمنت(24)عبارة موجهة لمعلمي اللغة العربية، وهي مؤلفة من (3) مجالات وهي على الترتيب: مجال اختيار التقنيات التعليمية- مجال استخدام التقنيات التعليمية- مجال استخدام الأجهزة التعليمية، وتم التأكد من صدقها وثباتها ومن ثم طُبّقتْ على عينة مؤلفة من(163) مدرساً ومدرسة بواقع (60) مدرساً و(103) مدرسات، و قد أظهرت نتائج البحث أن درجة توافر كفايات تقنيات التعليم ومستوى ممارستها كانت بدرجة عالية في المجالات كلّها، ولم تصل إلى درجة عالية جداً، كما توصلت نتائج الدراسة إلى وجود فروق بين متوسط درجات أفراد عينة الدراسة(الذكور، الإناث) في توافر تقنيات التعليم ومستوى ممارستها، لصالح الذكور، ووجود فروق بين متوسط درجات أفراد العينة تبعاً لسنوات الخبرة لصالح سنوات الخبرة من(1-5). The study has intended to find out the degree of competences of using instructional technology for the teachers of Arabic language in the second level of the basic learning within the schools of Damascus city and the extent of its application. In order to achieve the study's purposes, the researcher designed a questionnaire including 24 statements targeting the teachers of Arabic language. The questionnaire includes three parts: the choice of instructional technology, the scope of using instructional technology and the area of using learning devices. The study was reviewed and proved then applied to a sample of 163 teachers (60 males and 103 females). The Results of the study have revealed that the scope of instructional technology competences and application was high in all fields. The study has concluded that there are differences in the average degrees of the study sample (male, female) regarding the competences and application of instructional technology in favor of males. Also, there are differences between the average degrees of members of the study sample depending on years of experience in favor of experience years from 1 to 5.